(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Artificial intelligence (AI) poses both challenges and opportunities for media freedom in Europe. The interplay between EU legislation – including the Media Freedom Act, the AI Act, and the Regulation on political advertising – and the European Charter and ECHR seeks to protect media pluralism and democracy amid rapid digital transformation. AI’s growing role in content creation and distribution raises concerns over autonomy and editorial independence, but EU law aims to ensure transparency, AI literacy, and safeguards against undue influence. Cooperation between the EU and the Council of Europe through frameworks like the AI Convention reinforces a safe approach to innovation, promoting digital strategic autonomy for the EU.